Safety assessment of a novel, dietary pyrroloquinoline quinone disodium salt (mnemoPQQ®). (22nd November 2022) - Shiojima, Yoshiaki; Deshmukh, Narendra; Moriyama, Hiroyoshi; Soman, Yogini; Nalge, Prashant; Randhe, Manisha; Kanhere, Jaideep; Karmarkar, Aasavari; Bagchi, Manashi; Bagchi, Debasis
Abstract: Pyrroloquinoline quinone (PQQ), a potent coenzyme antioxidant naturally occurring in foods, has been demonstrated to protect brain cells by enhancing the expression of nerve growth factors (NGF) and NGF receptors, and suppressing the fibril formation and aggression of amyloid β. We developed mnemoPQQ ®, a novel PQQ disodium salt and assessed its safety in GLP compliant toxicity studies. Acute toxicity studies of mnemoPQQ ® in Wistar rats revealed that its LD50 was 1825- and 1410 mg/kg body weight (bw) in male and female rats, respectively, whereas its acute dermal LD50 was >2000 mg/kg bw. mnemoPQQ ® was found to be nonirritant to the skin of rabbit in an acute dermal irritation/corrosion study, and classified mnemoPQQ ® as a nonirritant to the eye of rabbit in an acute eye irritation/corrosion study. Ames bacterial reverse mutation assay and in vitro Mammalian cell gene mutation test exhibited its non-mutagenic potential. In mammalian in vivo erythrocyte micronucleus test, mnemoPQQ ® was classified as non-clastogenic and non-mutagenic. A 90-day sub-chronic toxicity study, conducted at and up to the highest daily dose of 600 mg/kg body weight, revealed no evidence of systemic toxicity. All rats survived the treatment without any significant abnormal clinical signs and alterations in hematology, clinical chemistry, neurological evaluation, thyroid functions, reproductive hormone levels, sperm evaluations, vaginal cytology, endocrine functions, organ weight and gross and microscopic pathology findings. No observed adverse effect level (NOAEL) of mnemoPQQ ® was found to be greater than 600 mg/kg body weight. These studies affirm that mnemoPQQ ® has broad spectrum safety for human consumption.